2014
DOI: 10.1021/nl404815q
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Cytocompatible Ferrite Coatings Facilitate the Realization of a Nanovoyager in Human Blood

Abstract: Controlled motion of artificial nanomotors in biological environments, such as blood, can lead to fascinating biomedical applications, ranging from targeted drug delivery to microsurgery and many more. In spite of the various strategies used in fabricating and actuating nanomotors, practical issues related to fuel requirement, corrosion, and liquid viscosity have limited the motion of nanomotors to model systems such as water, serum, or biofluids diluted with toxic chemical fuels, such as hydrogen peroxide. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 46 publications
2
137
0
Order By: Relevance
“…By integration of a conformal ferrite coating, Venugopalan et al reported a cytocompatible magnetically driven helical micromotor that can be propelled in human blood at negligible dilutions. 237 Furthermore, Nelson and co-workers have designed a platform for the biomedical application of magnetically driven motors in the eye. 238 The possibility of targeted retinal drug delivery, 239 retinal vein cannulation, and oxygen sensing 240 with the use of magnetic microrobots has been demonstrated.…”
Section: Toward Applicationmentioning
confidence: 99%
“…By integration of a conformal ferrite coating, Venugopalan et al reported a cytocompatible magnetically driven helical micromotor that can be propelled in human blood at negligible dilutions. 237 Furthermore, Nelson and co-workers have designed a platform for the biomedical application of magnetically driven motors in the eye. 238 The possibility of targeted retinal drug delivery, 239 retinal vein cannulation, and oxygen sensing 240 with the use of magnetic microrobots has been demonstrated.…”
Section: Toward Applicationmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/379024 doi: bioRxiv preprint first posted online Jul. 28, 2018; rotation of bacterial flagella, and the beating of paramecium cilia, which have so far inspired many synthetic swimmer designs (26)(27)(28)(29)(30)(31). Inspired by a similar mechanism, the design of our microrobotic swimmer is illustrated in Fig.…”
Section: Design Fabrication and Mobility Of Microswimmersmentioning
confidence: 99%
“…42 Such a high degree of crystallographic inversion can alter the crystal symmetry as well as the spin structure, and may thereby induce a higher anisotropy and an enhanced f FMR as a consequence. Although it is in its infancy, this approach can be an excellent way to modulate ferromagnetic resonance frequency of spinel ferrites via the soft-chemical route.…”
Section: Fig 3 (A) Processing Steps For Zinc Ferrite Thin Film Depomentioning
confidence: 99%